Phenomenology of psychiatric emergencies - Goretti, Stefano; Esposito, Cecilia Maria; Di Petta, Gilberto (Frontiers in Psychology, 2023)
Psychiatric urgency is defined as a situation of serious mental suffering and behavioral alteration, which promptly requires adequate treatment. Even if until now neglected by phenomenological psychopathology, the emergency issue faces a clinical management challenge in which the phenomenological method becomes fundamental. The purpose of this manuscript is then to explore the phenomenological perspective of psychiatric emergencies. The encounter in clinical phenomenology is seen as an encounter between two men, where the transformative power of understanding reverberates from both sides. The approach to the other must be respectful, along the lines of the ethics of approximation. If clinicians are not sufficiently trained in the encounter, the risk is to get stuck in the anguish of the instant, to become its tools. It is precisely the atmosphere of the emergency room that is full of expectations, anxiety, which hinders the possibility of encountering. Instead, this possibility must be recovered, because the encounter is the founding aspect of every clinical resolution. It means for the clinician to position himself not outside the crisis, but to immerse himself in the patient's life-world. Only then will the explosiveness of his symptoms appear to us not only as a symptomatic cascade to be contained and extinguished, but as the expression of a life-world in crisis. Psychiatric crisis is always a situation in which we are thrown, perhaps to the highest degree. Even in the absence of an adequate setting the phenomenological method retains its panoramic gaze intact.